(untitled) (Journal of the College of Basic Education, 2022)
The impact of the diversity of directorial visions on contemporary theatrical trends and movements is wideningAesthetic requirements for the structure of theatrical discourse + which led to the displacement of componentspresentation and its elements; Including the narrative system of the text that was formed in the beginnings of the theaterThe geography of the theatrical performance and the theoretical and intellectual basis that provides most of the theatrical performanceits aesthetic flow and transcendental element to other display elements; And in subsequent developmentsTheatrical director withdrew from the domination of the textual structure to deeper and more intense rangesaesthetic; Thus, a new concept called "text processing" was formed.